Managing chromoblastomycosis with acitretin plus imiquimod: A case report on the improvement of cutaneous lesions and reduction of the treatment time - Belda, Walter; Casolato, Ana Thereza Stradioto; Luppi, Juliana Bronzato; Passero, Luiz Felipe Domingues [UNESP] (Wiley, 2021)
Chromoblastomycosis (CBM) is an infectious disease caused by fungi that is prevalent in tropical and subtropical countries. Besides few therapeutic options, the classical treatment of CBM needs to be administrated for a long period of time, and unfortunately some patients do not show improvement of the lesions. Thus, it becomes urgent to develop new strategies for the treatment of CBM. This work reports a successful treatment, performed with the combination of oral acitretin (50 mg/kg, once a day) plus topical imiquimod (50 mg/g, five times per week) for 5 months in a patient with CBM. A significant improvement of the lesions was observed in the 1st month, and in the 5th a complete regression of lesions was recorded. Changes in the biochemical parameters were not observed. These data suggest that the combination of acitretin and imiquimod may be effective at treating CBM.
Keywords: acitretin; chromoblastomycosis; imiquimod; lesion evolution; treatment